Lack of polymorphism in NRAMPI gene exon V-VII region in Murrah buffaloes as explored by PCR-RFLP - Parveen Kumar,; Sangwan, M.L.; Aman Kumar,; T. Nanda,; Subhash Chander, (Journal of Livestock Biodiversity, 2025)
The present study was conducted on 50 Murrah buffaloes (20 were seropositive for brucellosis). DNA from blood samples was isolated using Sambrook and Russel method. An attempt was made to study the polymorphic pattern of NRAMP1(Natural resistance associated macrophage protein) gene with 959 by region of exon V-VI I through PCR RFLP using AluI, HaeIII, RsaI, StyI and TaqI restriction enzymes. All restriction enzymes showed monomorphic pattern viz. xx, aa, bb, cc, and dd respectively which revealed that there was no polymorphism in this region in Murrah buffaloes. It is inferred that there was no selective advantage of Exon V-VII part of NRAMP1 gene in respect of disease resistance.